Engendering Violence in Papua New Guinea 2012
DOI: 10.22459/evpng.07.2012.04
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Mary: Marian Devotion as a Solution to Gender-based Violence in Urban PNG

Abstract: This chapter deals with how, in the urban setting of Madang in Papua New Guinea, Marian devotion is deployed in response to gender-based violence, including in the context of HIV. 1 While providing insight into the lived religious experiences of Catholic women and, in particular, female members of the Legion of Mary, this chapter shows how women seek help from Mary and God in order to find a solution to the everyday violence they face. The experiences and perceptions described here reveal women's engagement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…327 The 'custom' honoured in such courts is an '"adapted" form of custom', 328 reflecting 'the presence and importance of influential local mores' 329 among western Pacific peoples but also 'intermingled with Western processes and procedures'. 330 Hermkens (2012) and others have documented so powerfully, women were critical to these efforts, and as Saovana-Spriggs argues used their particular position as 'mothers of the land', not just as mothers of individual soldiers but as nurturers of people and place, by deploying their powers, especially in matrilineal parts of Bougainville to intervene between combatants and make peace. But as several authors have demonstrated, as the peace-written from the perspective of a young Bougainville Revolutionary Army soldier whose wife had been raped by men of the Papua New Guinea Defence Force.…”
Section: Resultsmentioning
confidence: 99%
“…327 The 'custom' honoured in such courts is an '"adapted" form of custom', 328 reflecting 'the presence and importance of influential local mores' 329 among western Pacific peoples but also 'intermingled with Western processes and procedures'. 330 Hermkens (2012) and others have documented so powerfully, women were critical to these efforts, and as Saovana-Spriggs argues used their particular position as 'mothers of the land', not just as mothers of individual soldiers but as nurturers of people and place, by deploying their powers, especially in matrilineal parts of Bougainville to intervene between combatants and make peace. But as several authors have demonstrated, as the peace-written from the perspective of a young Bougainville Revolutionary Army soldier whose wife had been raped by men of the Papua New Guinea Defence Force.…”
Section: Resultsmentioning
confidence: 99%
“…A minority even suggested (somewhat sheepishly) that their Christianity was more a remnant influence from their childhoods than an active and ongoing part of their lives. Nevertheless, whether they were strong, practising Christians or not, among this cohort, there is a general consensus that Christianity promotes gender equity rather than female subordination (Hermkens 2012). As Susan put it, 'I want them [men] to know that God created us equal and there's no preference that man should take the upper hand' (interview, Susan, aged 22, Port Moresby, December 2007).…”
Section: The Importance Of Financial Autonomymentioning
confidence: 96%
“…We want to interrogate, in this volume, a proposition that the containment of gender in the body is an essential part of the process of establishing the Christian individual in Melanesia. Hermkens’ () work on Mary devotion in PNG as a way of dealing with female submission to men and male violence is useful in this regard. In her study Hermkens outlines the way the PNG Mary worshippers point out the necessity of ‘internalizing Mary’, of ‘becoming Mary’, and also internalising her virtues.…”
Section: Bringing New Conceptualisations Into the Anthropology Of Chrmentioning
confidence: 99%
“…Through their testimonials, women create an arena for creative performance and communication, in spite of not being allowed the formal preacher roles in church. It is also from within this paradigm that we receive analyses of women's resistance and empowerment (see Hermkens ; Jolly ). However, we know from insights into Islam and female devotion that these analyses risk taking the concept of the individual and ‘liberation’ for granted (see for instance Mahmood ).…”
Section: Bringing New Conceptualisations Into the Anthropology Of Chrmentioning
confidence: 99%